FEATURES OF TEACHING PREPOSITIONAL CONTROL TO STUDENTS IN RUSSIAN AS A FOREIGN LANGUAGE CLASSES - Rustam Egamov; Uktamboy Kalandarov (Bright Mind Publishing, 2025)
The article considers the problem of methods of teaching Russian prepositions in the process of teaching Russian to students. The main objective of the article is to determine the most productive methods of studying Russian prepositions in Russian as a foreign language classes. The article shows that the semantics of a preposition is revealed in the process of its combination with various lexemes. Since words combined with prepositions can affect their meaning, it is necessary to study the semantics of the prepositional-case construction as a whole.
Keywords: Frequency of use, spatial relations, lexeme, semantics of prepositions, optimization of the learning process, typical models.